EPIDEMIOLOGICAL PROFILE OF PEDIATRIC BURNS IN BRAZIL: A SYSTEMATIC REVIEW WITH META-ANALYSIS - Zamuraym, Isabella de Menezes; Rodrigues, Thais Miranda; Lima, Philippe de Oliveira; Xavier, José Emerson; da Silva, Jaiurte Gomes Martins; Araujo, Diego Neves; Miguel , Rafael Danyllo da Silva; Galdino, Mônica Roseli Brito (ARACÊ, 2025)
Aim: This study aimed to determine the epidemiological profile of burns in Brazilian children, based on a systematic review with meta-analysis. Methods: The search followed the PRISMA guidelines, the protocol was registered in PROSPERO and we used STROB to investigate risk of bias. For meta-analysis, R-studio was used, adopting the random distribution model, the chi-square (X12) and I-square (I2) tests to verify heterogeneity and its amplitude, respectively. Results: Eleven studies were included for qualitative analysis and 4 for meta-analysis. Only one study presented a high risk of bias. The main body area affected by burns was the trunk, 77% (95% CI 0.15–0.98; X12 = 30.52, p < 0.001; I2 = 97%) of which are second-degree (95% CI 0.80–0.94; X12 = 4.55, p = 0.03; I2 = 78%) scald injuries (95% CI 0.56–0.68; X12 = 0.22, p = 0.64; I2 = 0%). Males were the most affected (95% CI 0.53–0.65; X12 = 1.62, p = 0.20; I2 = 38%), and the most prevalent age group was the one aged between 0-5 years (95% CI 0.72–0.83; X12 = 1.47, p = 0.22; I2 = 32%). Conclusion: This study characterized the epidemiological profile of childhood burns, pointing out the prevalence according to age, sex, affected areas and causal agents of these injuries.